2020
DOI: 10.1002/dev.22055
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the hormonal and neural correlates of paternal protective behavior to their infants

Abstract: Infant protection is an important but largely neglected aspect of parental care. Available theory and research suggest that endocrine levels and neural responses might be biological correlates of protective behavior. However, no research to date examined associations between these neurobiological and behavioral aspects. This study, preregistered on https://osf.io/2acxd, explored the psychobiology of paternal protection in 77 new fathers by combining neural responses to infant‐threatening situations, self‐repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 55 publications
4
16
0
Order By: Relevance
“…In one correlational study AVP was associated with fathers' stimulatory interaction with their infants [ 17 ]. In another study AVP was unrelated to fathers' neural or behavioural responses to infant threatening situations [ 18 ]. However, administration of AVP affected neural and behavioural responses of expectant fathers to sounds of crying infants [ 19 , 20 ], pointing to a role for AVP in responding to infant distress, one of the key requirements for sensitive caregiving.…”
Section: Introductionmentioning
confidence: 99%
“…In one correlational study AVP was associated with fathers' stimulatory interaction with their infants [ 17 ]. In another study AVP was unrelated to fathers' neural or behavioural responses to infant threatening situations [ 18 ]. However, administration of AVP affected neural and behavioural responses of expectant fathers to sounds of crying infants [ 19 , 20 ], pointing to a role for AVP in responding to infant distress, one of the key requirements for sensitive caregiving.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying potential threats for the child’s safety has been found to trigger brain activity in the amygdala in expectant fathers ( Van’t Veer et al. , 2019 ) and new fathers ( Lotz et al. , 2020 ) when they were exposed to infant-threatening videos.…”
Section: Discussionmentioning
confidence: 99%
“…Although the neurobiological base of parental protection is still largely unexplored territory, two previous studies reported activation of the amygdala and the salience network among expectant and first‐time fathers while viewing videos of infant‐threatening (vs. neutral) videos 3,4 . Additionally, activation in the visual cortex and in regions previously characterized as part of the parental care network, including the superior frontal gyrus and precentral gyrus, was observed.…”
Section: Introductionmentioning
confidence: 94%
“…Given this evolutionary importance, it is likely that specific neural systems have evolved to anticipate and respond to potential threats to infant's safety. Indeed, previous studies exploring the neural base of paternal protection indicate that observing infant‐threatening situations elicits activation in the salience network, 3,4 including the insula and anterior cingulate gyrus, and the amygdala, a region important for fear and threat‐processing 5 . However, similar to other dimensions of caregiving, parents may vary in their degree of protection.…”
Section: Introductionmentioning
confidence: 99%